European Resuscitation Council Guidelines 2021: Newborn resuscitation and support of transition of infants at birth. (April 2021) - Madar, John; Roehr, Charles C.; Ainsworth, Sean; Ersdal, Hege; Morley, Colin; Rüdiger, Mario; Skåre, Christiane; Szczapa, Tomasz; te Pas, Arjan; Trevisanuto, Daniele; Urlesberger, Berndt; Wilkinson, Dominic; et al.
Abstract: The European Resuscitation Council has produced these newborn life support guidelines, which are based on the International Liaison Committee on Resuscitation (ILCOR) 2020 Consensus on Science and Treatment Recommendations (CoSTR) for Neonatal Life Support. The guidelines cover the management of the term and preterm infant. The topics covered include an algorithm to aid a logical approach to resuscitation of the newborn, factors before delivery, training and education, thermal control, management of the umbilical cord after birth, initial assessment and categorisation of the newborn infant, airway and breathing and circulation support, communication with parents, considerations when withholding and discontinuing support.